Lived realities of solo motherhood, donor conception and medically assisted reproduction - Ravn, Tine (Emerald Publishing Limited, 2021)
This book explores the empirical manifestations of the paradoxical features of reproductive technologies and provides in-depth understandings of solo motherhood through assisted reproduction and by recognising the complex experiences and the lived realities of forming donor-conceived families. The author offers insights into how single women 'do' family, identity and kinship and how the choice to create life as a solo mother is continuously rationalised. She uncovers how established, societal cultural narratives are adopted, negotiated and transformed in the processes of decision-making and fertility treatment. The book draws on science and technology studies, feminist theory, kinship- and family studies and identity theory, and reveals how aspects of bio-genetic and social connections (nature-culture) take on varying meanings when kinship and familial relations - are created through assisted reproduction. Through the lens of solo mother families, the book covers broader sociological questions including; how donor conception challenges existing and endemic kinship ideas and practices and what kinds of individual, social and legal responses have been prompted by advances within medically assisted reproduction.
Keywords: Single mothers.; Artificial insemination, Human -- Social aspects.; Social Science -- Sociology / Marriage & Family.; Sociology: birth.; elektronické knihy; electronic books